Disaster Vulnerability, Hazards and Resilience 2015
DOI: 10.1007/978-3-319-16453-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Resilience

Abstract: This chapter explores the importance of understanding how social aspects like communication and social capital impact community resilience and infl uence the various public, private, and non-profi t agencies that respond to crises. It also explores the perceptions of emergency management personnel in communicating with the public during a disaster situation. Keywords IntroductionEffective communication is important during each phase of emergency management. In the mitigation and preparedness phases, communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This option is one of the elements of the relevance and efficiency of communications plans for the resilience of cities to flood risks. Communication for resilience to climate change is increasingly addressed in scientific literature (Doerfel et al, 2022;Ling et al, 2022;Carr et al, 2016;Rivera et al, 2015;Kellens et al, 2012;Wachinger et al, 2012). The B 2 CresCom scientific framework is characterized by its approaches, its tools and its information families that are oriented by the results of engagement, mobilization, participation and contribution of urban populations to flood resilience policies of cities success.…”
Section: Discussionmentioning
confidence: 99%
“…This option is one of the elements of the relevance and efficiency of communications plans for the resilience of cities to flood risks. Communication for resilience to climate change is increasingly addressed in scientific literature (Doerfel et al, 2022;Ling et al, 2022;Carr et al, 2016;Rivera et al, 2015;Kellens et al, 2012;Wachinger et al, 2012). The B 2 CresCom scientific framework is characterized by its approaches, its tools and its information families that are oriented by the results of engagement, mobilization, participation and contribution of urban populations to flood resilience policies of cities success.…”
Section: Discussionmentioning
confidence: 99%
“…A highly significant finding is that 12 of 16 participants who responded to the survey indicated that the event had highly increased their trust in the government. This matter is of considerable significance for two interrelated reasons: public confidence is an essential element for maintaining resilience in the face of an emergency [39][40][41], and public confidence in many jurisdictions (including Israel) has suffered for various reasons (the examination of which requires a different study) [42,43]. The matter of access to novel data was also reflected by several of the participants' comments as one of the key features that made the Datathon worth their while.…”
Section: Main Findingsmentioning
confidence: 99%
“…Given the dynamic nature of events caused by natural hazards, emergency organizations often need to adjust beyond their usual structures to effectively respond to these complex situations, addressing new challenges and tasks (Andreassen & Borch, 2020). Responding to such events requires collaboration between organizations because a single organization may not respond independently due to rapid changes in the environment, a lack of experience, the scope of the task, and insufficient resources (Boin & Rhinard, 2023;Rivera & Kapucu, 2015). Interorganizational collaboration can be ensured by each organization systematically sharing their goals and the information they have (Therrien et al, 2015).…”
Section: Introductionmentioning
confidence: 99%